Compact nine‐band antenna for 4G/5G smartphones. Issue 4 (22nd October 2018) - Huang, Daiwei; Du, Zhengwei
Abstract: This article presents a nine‐band antenna whose size is 70 mm × 7 mm × 5.8 mm for 4G/5G smartphones. The proposed antenna consists of a T‐shape coupled line and two ground branches. The T‐shape coupled line is used to produce the resonances at about 925 and 2900 MHz respectively. One ground branch along with the T‐shape coupled line is used to cover the lower band (698‐960 MHz), and the other ground branch is used to cover the 3.6 GHz band (3400‐3800 MHz). By using the higher order modes of the T‐shape coupled line and the ground branches, the higher band (1710‐2690 MHz) is covered. The advantage of the proposed antenna is that a nine‐band antenna can be realized with an only 7 mm ground clearance and without using any lumped element. A prototype is manufactured and measured. According to the measured results, at the bands of 0.693‐0.98 GHz, 1.69‐2.94 GHz, and 3.05‐4 GHz, the S11 are smaller than −6 dB. The −6 dB impedance operating frequency band of the proposed antenna can cover the LTE700, GSM850, GSM900, DCS, PCS, UMTS, LTE2300, LTE2500, and 3.6 GHz bands. The simulated and measured results of the radiation performance also are presented.